2FYSH: two-factor authentication you should have for password replacement - Sunderi Pranata; Hargyo Tri Nugroho (Universitas Ahmad Dahlan, 2019)
Password has been the most used authentication system these days. However, strong passwords are hard to remember and unique to every account. Unfortunately, even with the strongest passwords, password authentication system can still be breached by some kind of attacks. 2FYSH is two tokens-based authentication protocol designed to replace the password authentication entirely. The two tokens are a mobile phone and an NFC card. By utilizing mobile phones as one of the tokens, 2FYSH is offering third layer of security for users that lock their phone with some kind of security. 2FYSH is secure since it uses public and private key along with challenge-response protocol. 2FYSH protects the user from usual password attacks such as man-in-the-middle attack, phishing, eavesdropping, brute forcing, shoulder surfing, key logging, and verifier leaking. The secure design of 2FYSH has made 90% of the usability test participants to prefer 2FYSH for securing their sensitive information. This fact makes 2FYSH best applied to secure sensitive data needs such as bank accounts and corporate secrets.